MHD Turbulence Studies Using Lattice Boltzmann Algorithms (Communications in Computational Physics, 2008)
Three dimensional free-decaying MHD turbulence is simulated by lattice Boltzmann methods on a spatial grid of 80003 for low and high magnetic Prandtl number. It is verified that ∇·B=0 is automatically maintained to machine accuracy throughout the simulation. Isosurfaces of vorticity and current show the persistence of many large scale structures (both magnetic and velocity) for a long time — unlike the velocity isosurfaces of Navier-Stokes turbulence.